Indices of diet quality among Polish and Spanish physical education students - Maria Gacek; Grażyna Kosiba; Agnieszka Wojtowicz; Guillermo Felipe López Sánchez; Jacek Szalewski (Journal of Kinesiology and Exercise Sciences)
Introduction: A healthy diet is an important factor in implementing health, and the way of eating depends on individual and environmental factors. Objective: The aim of the study was to assess diet quality indices among Polish and Spanish physical education students depending on country of residence and gender. Materials and methods: Research was carried out among 219 students from Poland and 280 from Spain. A questionnaire was used to evaluate views on eating and nutritional habits (Kom-PAN). Based on the daily frequency of consuming specific groups of products, 2 indices were calculated: the pro-healthy diet index (pHDI-10) and non-healthy diet index (nHDI-14). Two-way ANOVA was used for statistical analysis. The level of significance was set at p=0.05. Results: The values of the pro-healthy (pHDI-10) and non-healthy diet (nHDI-14) indices in the group of students were 4.65 and 4.05 (times/day), respectively, which means a low level of both favourable and unfavourable food choices. Students from Poland, regardless of gender, showed a higher level of eating a healthy diet (pHDI-10) than students from Spain. However, the level of the non-healthy diet index (nHDI-14) between students from Poland and Spain differed by gender (p<0.001). In the Polish group, men obtained a higher nHDI-14 index than women (p<0.001), while in Spain, these values were at the same level. Furthermore, it was found that differences between countries occurred only in men, with students from Poland obtaining higher values of the nonhealthy diet index (nHDI-14) than those from Spain (p<0.001), while students from both countries demonstrated similar values. Conclusions: Low levels of healthy and unhealthy diet indices were demonstrated in Polish and Spanish physical education students, with the quality of diet differentiated by country and gender.